(untitled) (Communication & Society, 2020)
Political trust is essential for a democratic regime to work, and a declining asset in Western countries. It has been confirmed theoretically and empirically that news media are an important source of influence on political trust, though literature have not considered social media, in which the circulation of false or misleading information, and propaganda, might have a negative effect on political trust, to be relevant channels of news consumption. In order to explore the effect of social media on political trust in comparison with that of traditional media, an ANOVA test and hierarchical multiple linear regression models were run on a three-wave panel survey, during the presidential elections of 2018 (N = 701) in Mexico. The findings indicate that the election campaign had a positive effect on institutional trust, growing as the campaign developed, and that there was a positive influence from social media, followed by television.